2016
DOI: 10.5539/ijbm.v11n6p70
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Management Processes and Their Impact on Organizational Performance, the Adoption Balanced Scorecard: The Moderating Role of Quality Assurance Standards—An Applied Study on Private Jordanian Universities

Abstract: The study aims to identify the knowledge management processes and their impact on the organizational performance in the Jordanian private universities, the impact of knowledge management on organizational performance was tested next. Finally, the quality assurance standard as a moderating variable was studied.The study was conducted on Jordanian private universities with a stratified proportionate random sample consisted of (334) faculty members. Questionnaires were distributed to the sample to collect the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 16 publications
(7 reference statements)
0
6
0
3
Order By: Relevance
“…In an explanatory research program, AL-Hayaly and Alnajjar [32] found that knowledge processing plays an important role in enhancing output by hypothesis testing. Abdela [9] established that acquisition of information has a significant effect on the organizational efficiency as Ahmed, Fiaz, and Shoaib [33], using concise research findings indicate that the acquisition of knowledge contributes to a high degree of customer satisfaction through quality customer services.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In an explanatory research program, AL-Hayaly and Alnajjar [32] found that knowledge processing plays an important role in enhancing output by hypothesis testing. Abdela [9] established that acquisition of information has a significant effect on the organizational efficiency as Ahmed, Fiaz, and Shoaib [33], using concise research findings indicate that the acquisition of knowledge contributes to a high degree of customer satisfaction through quality customer services.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Performance [32] exposed that In the first instance, the organisation establishes the capacity to understand the necessary frameworks for the characteristics found in the areas of concern. On the basis of these results, they showed that each of; accumulating external information to strengthen expertise of staff (M = 3.57; SD = 0.88), gaining knowledge through some kind of regular, tailored training of employees to (M = 3.53; SD = 0.83), and performing regular internal training of employees on information acquisition (M = 3.48; SD = 0.88) highly affects employee performance of Nairobi City Water and Sewerage Company.…”
Section: Acquiring Information and Employeementioning
confidence: 99%
“…Melalui berbagai pelatihan dan berbagi pengetahuan diharapkan dapat meningkatkan kualitas Sumber Daya Manusia yang pada akhirnya dapat meningkatkan kinerja pegawai. Kriteria kinerja pegawai mencapai hasil yang lebih maksimal apabila didukung dengan knowledge yang dimiliki dan berkontribusi terhadap pencapaian dan pengembangan kinerja organisasi (Al-Hayaly & Alnajjar, 2016).…”
Section: Pendahuluanunclassified
“…Manajemen pengetahuan atau lebih dikenal dengan istilah knowledge management pada dasarnya dapat diimplementasikan sebagai strategi dengan sedikit atau tanpa tergantung dengan teknologi yang canggih seperti sekarang ini. Secara umum, knowledge management merupakan sebuah proses yang mengkoordinasikan penggunaan informasi, pengetahuan dan pengalaman (Al-Hayaly & Alnajjar, 2016 Knowledge management telah diakui sebagai instrumen yang penting untuk mencapai tujuan khusus dari suatu organisasi dan bahkan suatu negara sehingga dapat mempertahankan pertumbuhan ekonomi serta keunggulan kompetitif (Ragab & Arisha, 2013). Knowledge Management merupakan langkah untuk menangkap, mengorganisasikan, penyimpanan pengetahuan, dan pengalaman dari setiapindividu pekerja atau group pekerja didalam sebuah organisasi dan membuat knowledge tersedia untuk pekerja lainnya di dalam organisasi (Zwain, Teong, & Othman, 2012).…”
Section: Pendahuluanunclassified
“…The study of knowledge sharing has done by Pai and Chang (2013); who found that knowledge absorption influences knowledge sharing activities. Knowledge sharing can drive improvements in innovation and organizational performance (Lin, 2007;Al-Hayaly & Alnajjar, 2016) The results of research conducted by Liao (2006) and Jaberi (2016) concluded that knowledge sharing activities positively affect the improvement of organizational innovation. The study results of Andreeva and Kianto (2011) found a positive relationship between knowledge sharing and innovation.…”
Section: Introductionmentioning
confidence: 99%